Pengaruh Senam Hamil Terhadap Pengurangan Nyeri Punggung Pada Ibu Hamil Di Praktek Mandiri Bidan Elisabeth Kabupaten Mandailing Natal Tahun 2022 - Surati Surati; Basaria Manurung (Jurnal Rumpun Ilmu Kesehatan, 2023)
Pregnancy is a period in which a woman carries an embryo or fetus in her body. The period of pregnancy starts from conception to the birth of the fetus. During pregnancy, the mother will experience physical and psychological changes. The physical changes that occur sometimes even cause discomfort for the mother, one of which is back pain. This study aims to determine the effect of Pregnancy Exercise on Reducing Back Pain in Pregnant Women at Elisabeth Midwife Independent Practice, Mandailing Natal District in 2022. This type of research is a quasi-experimental study with a research approach with a prepost test design with one group test. Population is all pregnant women in the Elisabeth Midwife Independent Practice, Mandailing Natal District in 2022, totaling 28 pregnant women. The number of samples used was 28 people obtained by using total sampling technique. The data analysis technique uses the Paired-Samples T Test. The results obtained in this study were from 28 respondents, there was an effect of pregnancy exercise on reducing back pain in pregnant women with a value of p = 0.000. Conclusion: there is an effect of pregnancy exercise on reducing back pain in pregnant women. It is recommended for health workers to improve counseling related to reducing back pain in pregnant women with pregnancy exercise.